Reinvestigating the clinical relevance of the m6A writer METTL3 in urothelial carcinoma of the bladder - Koch, Jonas; Neuberger, Manuel; Schmidt-Dengler, Martina; Xu, Jinyun; Coutinho Carneiro, Vitor; Ellinger, Jörg; Kriegmair, Maximilian; Nuhn, Philipp; Erben, Philipp; Michel, Maurice Stephan; Helm, Mark; Rodríguez Paredes, Manuel; et al. (iScience, 2023)
METTL3 is the major writer of N6-Methyladenosine (m6A) and has been associated with controversial roles in cancer. This is best illustrated in urothelial carcinoma of the bladder (UCB), where METTL3 was described to have both oncogenic and tumor-suppressive functions. Here, we reinvestigated the role of METTL3 in UCB. METTL3 knockout reduced the oncogenic phenotype and m6A levels of UCB cell lines. However, complete depletion of METTL3/m6A was not achieved due to selection of cells expressing alternative METTL3 isoforms. Systematic vulnerability and inhibitor response analyses suggested that uroepithelial cells depend on METTL3 for viability. Furthermore, expression and survival analyses of clinical data revealed a complex role for METTL3 in UCB, with decreased m6A mRNA levels in UCB tumors. Our results suggest that METTL3 expression may be a suitable diagnostic UCB biomarker, as the enzyme promotes UCB formation. However, the suitability of the enzyme as a therapeutic target should be evaluated carefully.